2023
DOI: 10.3390/psychiatryint4040030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown Effects on Mood: Impact of Sex, Age, and Underlying Disease

Pantea Kiani,
Pauline A. Hendriksen,
Jessica Balikji
et al.

Abstract: Coronavirus 2019 (COVID-19) lockdown periods had a significant negative impact on people’s lives and psychological well-being. However, the impact of lockdowns differed between individuals. This study aimed to identify vulnerable groups and investigated the relationship between mood and perceived immune fitness and the number and severity of coronavirus 2019 (COVID-19) symptoms during the first COVID-19 lockdown in the Netherlands. In addition, the impact of emotion regulation and other preventive measures was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A study by Socci et al [35] showed that the active activities of older volunteers in Italy during the pandemic period had a positive impact on their overall well-being. In the Netherlands, younger individuals reported a significantly greater negative impact of the pandemic on physical activity and being active than the older participants [36]. Thus, the study shows that not all older people were equally susceptible to the effects of COVID-19, and some people even saw an improvement in their well-being [37].…”
Section: Literature Reviewmentioning
confidence: 75%
“…A study by Socci et al [35] showed that the active activities of older volunteers in Italy during the pandemic period had a positive impact on their overall well-being. In the Netherlands, younger individuals reported a significantly greater negative impact of the pandemic on physical activity and being active than the older participants [36]. Thus, the study shows that not all older people were equally susceptible to the effects of COVID-19, and some people even saw an improvement in their well-being [37].…”
Section: Literature Reviewmentioning
confidence: 75%